Building Inclusive Political Citizenship in the Aftermath of Village Head Election through Amos Yong's Hospitality Concept - Daun Rara, Desi Indriyani (KINAA: Jurnal Kepemimpinan Kristen dan Pemberdayaan Jemaat, 2024)
Abstract: Indonesia as a pluralist country holds the principle of equal citizenship, which considers that every individual and community group has the same rights and obligations and adheres to a democratic system of government. One of the main platforms to determine the leader who will represent the will of the people is the village head election. However, after the village head election, conflicts or disputes often occur in various regions including Mamasa, West Sulawesi. This conflict can threaten community unity and integrity. Therefore, the author links the phenomenon of post-village head election conflicts with citizenship politics and Amos Yong's Hospitality theory. The author presents the concept of hospitality as a new approach to overcome post-village head election conflicts and encourage inclusion in society. The method used is a qualitative approach by observing the phenomenon or case study under study, and using literature review to support the analysis. The purpose of this paper is to enrich the understanding of civic politics, apply Hospitality theory, and encourage new thinking in overcoming post-village head election conflicts.   Keywords: Citizenship Politics, Conflict, Difference, Hospitality, Village Head Election.